Identifikasi Makna Ukiran Alang (Lumbung Padi) - yohanis padallingan; gidien aryo pongdatu (Universitas Muhammadiyah Enrekang, 2021)
The purpose of this research is 1) to know the background of the carvings of pa 'barre allo, pa' manuk londong, pa 'tedong and pa' don sponge 2) know the moral message of the carvings of pa 'barre allo, pa' manuk londong, pa 'tedong and pa' don sponge. This research was carried out in Lembang Sa'dan Ulusalu, Sa'dan District, North Toraja, for a one year. This research is expected to be useful to: 1) the community as input and reference material in developing knowledge and providing information about moral messages in Toraja carvings. 2) for tourists, namely as an ingredient to gain insight into the Toraja culture, especially for local and foreign tourists who are quantitatively slowing down the Toraja culture for the first time. 3) for the regional government, to supporting the regional government in the development and maximum use of the tourist potential that is present in Toraja carvings 4) for the tourism office, as a reference to tourism management 5), fo the pimary school students as a reference to moral values ​​and social values. The results of the study show that Toraja carvings or Passura 'Toraya' have long been known by the Toraja as a form of communication represented by symbols. Each of these symbols contains moral messages that the ancestors conveyed to their children and grandchildren so that their descendants and later always live in the noble values ​​of the Torasonga Royong culture and become a light for others and especially for pimary school students.